Effectiveness of Nano Chitosan and Nano Silica to Suppress the Growth of Fusarium oxysporum, the Cause of Twisting Disease on Shallot - Hersanti; Febrianti, Nisrina; Djaya, Luciana (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2023)
Effectiveness of Nano Chitosan and Nano Silica to Suppress the Growth of Fusarium oxysporum, the Cause of Twisting Disease on Shallot Shallot twisting disease caused by Fusarium oxysporum f.sp. cepae is one of the major diseases on shallot. Alternative fungicides such as nano-sized chitosan and silica can be applied as environmentally friendly control methods. The objectives of this study were to evaluate the ability of a single or mixture of nano chitosan and nano silica to inhibit the in vitro growth of F. oxysporum and reduce the development of twisting disease on shallot plants, as well as to determine their effective concentrations. The in vitro test was arranged in a completely randomized design, while the in vivo test was arranged in a randomized complete block design with 10 treatments and three replications. The treatments were application of single nano chitosan at 50 ppm, 100 ppm, 200 ppm, single nano silica at 50 ppm, 100 ppm, 200 ppm, mixture of nano chitosan 50 ppm + nano silica 50 ppm, mixture of nano chitosan 100 ppm + nano silica 100 ppm, control, and 200 ppm of fungicide mancozeb 80%. The results showed that all treatments, compared to control, were able to suppress the in vitro growth of F. oxysporum colonies, as well as the disease development on shallot plants. Application of single nano chitosan at 100 ppm, and the mixture of nano chitosan at 100 ppm + nano silica 100 ppm caused the highest inhibition of the colony growth of F. oxysporum, which were 85.2% and 81.3% respectively, comparable to the application of mankozeb (83.5%). The mixture of nano chitosan at 100 ppm + nano silica 100 ppm was effective in suppressing the development of shallot twisting disease on shallot plants. The suppression was 56.3%, comparable to mankozeb which was 50.5%.